2016
DOI: 10.1590/0074-02760160183
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional meglumine antimoniate for the treatment of localised cutaneous leishmaniasis: a retrospective review of a Brazilian referral centre

Abstract: Although intralesional meglumine antimoniate (MA) infiltration is considered an option for cutaneous leishmaniasis (CL) therapy and is widely used in the Old World, there have been few studies supporting this therapeutic approach in the Americas. This study aims to describe outcomes and adverse events associated with intralesional therapy for CL. This retrospective study reviewed the experience of a Brazilian leishmaniasis reference centre using intralesional MA to treat 31 patients over five years (2008 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 9 publications
5
31
0
Order By: Relevance
“…Although some studies report a lower cure rate, such as the intralesional application of meglumine antimoniate in Iran for L. major, with a low cure rate of 56% [20], other studies, particularly in Latin America, report cure rates that exceed 70% with similar efficacy to the systemic Glucantime, without showing statistically significant differences [7]. In Brazil, Vasconcellos et al reported a healing rate close to 80% in patients who received intralesional therapy, considerably reducing adverse effects and therapeutic expenditure [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies report a lower cure rate, such as the intralesional application of meglumine antimoniate in Iran for L. major, with a low cure rate of 56% [20], other studies, particularly in Latin America, report cure rates that exceed 70% with similar efficacy to the systemic Glucantime, without showing statistically significant differences [7]. In Brazil, Vasconcellos et al reported a healing rate close to 80% in patients who received intralesional therapy, considerably reducing adverse effects and therapeutic expenditure [8].…”
Section: Discussionmentioning
confidence: 99%
“…There are cases and series of cases in the literature of cutaneous leishmaniasis treated with intralesional antimonials showing divergent results, some with satisfactory results, with cure rates as high as 70-80% [7,8] and others with poor cure rates [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Specific treatment is thus almost mandatory. Patients with contraindications to systemic treatment, however, can benefit from IL MA treatment 3,8 . Recently, Soto et al 9 found that treatment with IL MA has comparable efficacy to treatment with IL pentamidine in Bolivian patients with cutaneous leishmaniasis caused by L. braziliensis.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of direct parasitological cure has ethical implications and is not considered safe. 19 Ethics. This study was approved by the Human Research Ethics Committee of the Pontificia Universidad Católica del Ecuador (CEISH-057-2016) and the Ministerio de Salud Publica del Ecuador (MSP-DIS-2015-0011-O).…”
Section: Methods and Patientsmentioning
confidence: 99%
“…15,16 In Brazil, studies reported a cure rate of 80%, 83.3%, and 77.7% in patients with the ulcerative variant of CL. [17][18][19] Reported here are the results of a study conducted in the subtropical region of the province of Pichincha of Ecuador where 21 patients with LRC lesions were treated IL with MA.…”
Section: Introductionmentioning
confidence: 99%